أنماط وبدائل تصميمية لتلبية متطلبات السكن البيئي الساحلي في سوريا - كيالي محمد نجيب; ودح هاني هاشـم; الدبس ميساء غانم (Latakia University Journal -Engineering Sciences Series, 2019)
إن ظهور النظريات الحديثة في العمارة أحدث تغيراً كبيراً في مسار وشكل تطور الهندسة المعمارية وفي إيقاع تقدمها, وهذا التغير تسبب في تغير قيم الملائمة بين البناء وبين مستخدميه. كما أنه سبب ظهور نمط واحد أو أسلوب واحد في البناء يمكن تطبيقه في أي بقعة من بقاع الأرض, ومن هنا تأتي أهمية العمل على إيجاد الصيغة المعاصرة للفكر المعماري الذي يستطيع إنتاج عمارة جديدة متوافقة بيئياً ومتلائمة مع العصر الحالي, وهذا الفكر يجب أن يستند إلى: 1ـ إن أي تنمية يجب أن تخضع لقواعد الاستدامة والحفاظ على البيئة وتطوير نوعية حياة الساكنين. 2ـ التصميم العضوي هو المنظور الأكثر ملائمة للتنمية المعاصرة ولا يقصد بالتصميم العضوي الأشكال المستمدة من الطبيعة, وإنما التصاميم المنسجمة مع البيئة والمتوافقة معها. 3ـ يمكن للمدينة القديمة بما تحمله من سمات وما تمتلكه من مزايا مواكبة للعصر الحالي أن تقدم مفردات معمارية يمكن إعادة توظيفها في عمارة المدن المعاصرة. 4ـ ضرورة إيجاد معايير ديناميكية تجعل من العمارة أكثر مرونة وتوافقية لتحاكي التطور السريع في المجتمع. 5ـ أن يتمتع نظام ضابطة البناء بالمرونة والاستجابة للتغيرات الدائمة في المجتمع. The emergence of modern theories in architecture has caused a big change in the course and shape of the architectural development and in the harmony of its progress. This change caused a further change in the values of the convenience between the building and its users. It also led to the emergence of one mode or style applicable in any place all over the world. It is therefore quite important to try to find the contemporary mode of the architectural concept that originates new construction, which is environmentally compatible and in harmony with the present age. This concept should be based on the following: 1. Any development should be governed by the rules of endurance and preservation of the environment and the development of the kind of living of the inhabitants. 2. The organic design is the perspective that is mostly suitable to the contemporary development. However, what we mean by the organic design is not the shapes derived from nature but rather the designs which are in harmony and compatible with the environment. 3. The old civilizations, with all their features and advantages accompanying the age, can be employed in the modern cities construction. 4. The need to find dynamic standards that make the architecture more flexible and compatible to match the development of the society. 5. The construction controlling system should enjoy flexibility and response to the continuous changes of the society.